The Rotokawa geothermal system, New Zealand: Hydrothermal minerals and punctuated evolution - Mark P. Simpson; Amando G. Morales; Isabelle Chambefort; Samantha Alcaraz; Shunsuke Moribe; Sarah D. Milicich; Fabian Sepulveda; Jeffrey W. Hedenquist (Journal of Volcanology and Geothermal Research, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Metals exposures and telomere length as a marker of DNA damage among electronic waste workers and a reference group - Mabel Sarpong Duah; Ibrahim Issah; Shirley V. Simpson; Serwaa A. Bawua; Duah Dwomoh; Joseph K. H. Bonney; Shinsaku Inomata; Thomas G. Robins; Niladri Basu; Arima Hiroaki; Julius N. Fobil (Environmental Science and Pollution Research, 2026)

A phylogenetic perspective on the performance of Lactococcus lactis as starter culture in milk and plant milks - Zheng Zhao; Yuxin Zhang; David J. Simpson; Michael G. Gänzle (Food Research International, 2025)

Dietary niches of endemic and range-expanding salmonids in the western Canadian Arctic - Darcy G. McNicholl; Colin P. Gallagher; Richard Gordon; Tyler Carmichael; Ryan McLeod; Joe Illasiak; Leona Kayotuk; Max Kotokak; Sarah Lord; Jasmine Brewster; Sarah Buckle; Cora-Lee Simpson; et al. (Environmental Biology of Fishes, 2025)
The cumulative effects of climate change are impacting Arctic species and facilitating increased interactions between Arctic and sub-Arctic species. Anadromous Arctic char Salvelinus alpinus and the northern Dolly Varden Salvelinus malma malma are endemic Arctic fishes vulnerable to the impacts of climate change, yet our understanding of the dietary niches they occupy is limited. The recent increased occurrence of sub-Arctic Pacific salmon ( Oncorhynchus spp.) in the western Canadian Arctic has raised concerns among Indigenous communities given the potential for competition with endemic fishes important for subsistence fisheries. Stable isotopes (δ 13 C and δ 15 N) were analyzed from Arctic char, Dolly Varden, and chum salmon Oncorhynchus keta , collected among four coastal Canadian Beaufort Sea locations. These fishes were captured during the summer of 2017 and 2019 during ongoing community-based fisheries monitoring programs in the Inuvialuit Settlement Region and Gwich’in Settlement Area. The trophic position of Arctic char and Dolly Varden indicates both species rely heavily on pelagic prey enriched in δ 15 N, consistent with a diet of marine forage fishes. Chum salmon occupied a trophic position > 3.0‰ below the char species, which reflects a diet comprised primarily of marine invertebrates. Isotopic niche analyses revealed chum salmon do not overlap in diet with the char species during the summer marine foraging season, and thus were unlikely to compete for prey as adults. This assessment of dietary overlap informs conservation and fisheries co-management objectives of endemic fishes as their as interactions with range-expanding species become more prevalent within a rapidly changing Arctic.

The Blue Carbon Cost Tool – understanding market potential and investment requirements for high-quality coastal wetland projects - Stefanie Simpson; Lindsey S. Smart; Emily Landis; Stephanie Van Laere; Abu S. M. G. Kibria; Olga Albot; Mark Beeston; Catherine E. Lovelock; Robert I. McDonald; Ryan P. Moyer; Thomas A. Worthington; Tania L. Maxwell; et al. (Frontiers in Marine Science, 2025)
Blue carbon ecosystems, such as mangroves, tidal marshes, and seagrasses, are important for climate mitigation. As carbon sinks, they often exhibit higher per hectare carbon storage capacity and sequestration rates than terrestrial systems. These ecosystems provide additional benefits, including enhancing water quality, sustaining biodiversity, and maintaining coastal resilience to climate change impacts. The widespread loss of blue carbon ecosystems due to anthropogenic activities can contribute to increasing carbon emissions globally. Monetizing blue carbon through carbon credits offers an avenue to generate revenue and incentivize conservation and restoration efforts. However, limited data on project costs and carbon benefits make prioritization of blue carbon projects challenging. To address these challenges, we have developed, in collaboration with blue carbon experts, the Blue Carbon Cost Tool. This is a user-friendly interface enabling comparison of three core market project components – 1) carbon credit estimation, 2) project cost estimation, and 3) a qualitative, non-economic feasibility assessment – to assess and compare potential for blue carbon projects. Tool simulations with data available from nine countries demonstrate (a) how factors such as country, ecosystem type and project scale drive variability, (b) the need for local or project-specific data to enhance accuracy and reduce uncertainty, particularly in tidal marsh and seagrass systems, and (c) that higher price tolerance or upfront capital is needed to bridge implementation and maintenance cost gaps. The Blue Carbon Cost Tool can aid project developers and investors to better understand market opportunity and the resources needed to develop high quality blue carbon market projects.

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Combining analysis of individual and wastewater whole genome sequencing improves SARS-CoV-2 surveillance - Evan P. Troendle; Andrew J. Lee; Marina I. Reyne; Danielle M. Allen; Stephen J. Bridgett; Clara H. Radulescu; Michael Glenn; John-Paul Wilkins; Francesco Rubino; Behnam Firoozi Nejad; Cormac McSparron; Marc Niebel; et al. (Water Research, 2025)

Laboratory evaluation of potential climate change impacts on the larval metamorphosis of Pacific lamprey (Entosphenus tridentatus) - William G. Simpson; Timothy J. Blubaugh; Timothy A. Whitesel (Environmental Biology of Fishes, 2025)
Organisms that undergo metamorphosis can be particularly vulnerable to environmental changes. However, if these transitions are ignored as an explicit life stage in evaluations and models, such threats can be overlooked. In lamprey, larvae that achieve enough energy storage appear to metamorphose when exposed to cold winter water temperatures followed by a rise in spring temperature. Winters of the Pacific Northwest (USA) are experiencing climatic warming that may alter the conditions necessary for larval metamorphosis. Therefore, we conducted a laboratory study that compared the incidence of metamorphosis between larval Pacific lamprey ( Entosphenus tridentatus ) reared at natural winter river temperatures and those reared at water temperatures prevented from falling below 9 °C over 2 years. Repeating this experiment with two cohorts of larval lamprey resulted in no difference in the incidence of metamorphosis between temperature treatments in either rearing year. The group growth rate of cohort 1 larvae in the first year of laboratory rearing was greater than growth rates reported for stream-reared larvae, and more of these larvae metamorphosed in their first year compared to cohort 2. However, the incidence of metamorphosis was similar (about 78%) between both larval cohorts over 2 years, despite experiencing differences in collection years, temperature regimes, body sizes, and initial metamorphosis. We found no evidence that warming winter stream temperatures driven by climate change would limit Pacific lamprey metamorphosis the following summer. Subsequent work exploring whether individual growth and water temperature interact to influence near-term metamorphosis may allow managers to apply these results to other lamprey populations.

New Approach Needed To Address Declining Forestry Research Capacity And Relevancy in the US: A Call-To-Action - Robert G. Wagner; Alexander L. Friend; Emily J. Silver; Julio Rojas; Thomas R. Fox; Terry Baker; Robert Simpson (Journal of Forestry, 2025)
Recent dramatic reductions in research funding and personnel for university and government organizations by the new federal administration will reduce forestry research capacity in the coming years. However, these cuts only highlight the long-standing decline in forestry research capacity that has been occurring over the past several decades. These reductions will continue to impair the country’s ability to meet the scale and complexity of challenges facing US forests. At some point in the future, there will be an opportunity to rebuild and reshape forestry research capacity to address these challenges. Now is the time to plan the future of forestry research. Successfully rebuilding this capacity will require national support from a broad coalition of forest management organizations. Receiving this support will require substantially increasing the relevancy of research to forest managers relative to what has occurred in recent decades. We offer several suggestions for this rebuilding effort, including: 1) developing a periodic national survey of forest managers to clearly identify the most important problems they face on the ground, 2) regularly communicating results of the survey to forest researchers, program leaders of research funding agencies, policy makers, legislators, and others responsible for allocating forest research effort and funding, and 3) building on the science delivery successes of stakeholder-driven organizations such as the forest manager / university research cooperatives around the country.

Variations in Ecosystem‐Scale Methane Fluxes Across a Boreal Mire Complex Assessed by a Network of Flux Towers - Koffi Dodji Noumonvi; Mats B. Nilsson; Joshua L. Ratcliffe; Mats G. Öquist; Natascha Kljun; Johan E. S. Fransson; Järvi Järveoja; Anders Lindroth; Gillian Simpson; Jacob Smeds; Matthias Peichl (Global Change Biology, 2025)
High latitude mires are key ecosystems in the context of climate change since they store large amounts of carbon while constituting an important natural source of methane (CH 4 ). However, while a growing number of studies have investigated methane fluxes (FCH 4 ) at the plot‐ (~1 m 2 ) and ecosystem‐scale (~0.1–0.5 km 2 ) across the boreal biome, variations of FCH 4 magnitudes and drivers at the mesoscale (i.e., 0.5–20 km 2 ) of a mire complex are poorly understood. This study leveraged a network of four eddy‐covariance flux towers to explore the spatio‐temporal variations in ecosystem‐scale FCH 4 across a boreal mire complex in northern Sweden over 3 years (2020–2022). We found a consistent hierarchy of drivers for the temporal variability in FCH 4 across the mire complex, with gross primary production and soil temperature jointly emerging as primary controls, whereas water table depth had no independent effect. In contrast, peat physical and chemical properties, particularly bulk density and C:N ratio, were identified as significant baseline constraints for the spatial variations in FCH 4 across the mire complex. Our observations further revealed that the 3‐year mean annual FCH 4 across the mire complex ranged from 7 g C m −2 y −1 to 11 g C m −2 y −1 , with a coefficient of variation of 16% that is similar to the variation observed among geographically distant mire systems and peatland types across the boreal biome. Thus, our findings highlight an additional source of uncertainty when scaling information from single‐site studies to the mire complex scale and beyond. Furthermore, they suggest an urgent need for peatland ecosystem models to resolve the mesoscale variations in FCH 4 at the mire complex level to reduce uncertainties in the predictions of peatland carbon cycle‐climate feedbacks.

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Strain-level identification of bacteria persisting in food and in food processing facilities: when do two isolates represent the same strain and which tools identify a strain? - Vi D Pham; David J Simpson; Michael G Gänzle (Current Opinion in Food Science, 2025)

Vertebrates in trade that pose high invasion risk to the United States - Wesley M. Daniel; Helen R. Sofaer; Catherine S. Jarnevich; Richard A. Erickson; Brett A. DeGregorio; Peder S. Engelstad; Jonathan Freedman; Susan Canavan; E.M. Dean; Michael J. Adams; Charmayne L. Anderson; Mindy Barnett; et al. (Biological Conservation, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

LA-ICP-Q-MS/MS ReOs geochronology: A comparison of N2O and CH4 reaction gases - Alexander Simpson; Stijn Glorie; Sarah Gilbert; Renée Tamblyn; Michael G. Gadd (Chemical Geology, 2024)

Half a century of citizen science tag-recapture data reveals stock delineation and cross-jurisdictional connectivity of an iconic pelagic fish - Belinda K. Goddard; Tristan A. Guillemin; Hayden T. Schilling; Julian M. Hughes; Stephanie Brodie; Corey P. Green; Robert Harcourt; Charlie Huveneers; Daniel Ierodiaconou; Iain M. Suthers; Matthew D. Taylor; Sean R. Tracey; et al. (Reviews in Fish Biology and Fisheries, 2024)
Tag-recapture programs to monitor the movements of fish populations are among some of the longest-running citizen-science datasets to date. Here, using half a century of yellowtail kingfish ( Seriola lalandi, Carangidae) tag-recapture data collected through citizen-science projects, we report novel insights into population connectivity in Australia and New Zealand (NZ). Despite the importance of kingfish in commercial and recreational fisheries, substantial knowledge gaps about their stock structure and connectivity between jurisdictions hinder current management efforts. Between 1974 and 2022, 63,432 releases and 4636 recaptures (7.3%) of tagged kingfish were collected in Australia and NZ. Most tagged individuals (51.4%) were recaptured within 10 km of their original release location up to 14 years post-release (mean: 225 days), indicating some degree of site fidelity. However, 656 (14.2%) kingfish were recaptured over 100 km from their release location, with one fish travelling at least 2834 km in 702 days. Seasonal variability was evident for releases and recaptures, with more releases occurring in summer and autumn in most jurisdictions. Network analysis of recaptures revealed no connectivity between tagged kingfish from western and eastern Australia, supporting genetic delineation. By contrast, extensive connectivity exists across eastern Australia and NZ, with 87 kingfish moving between five Australian state jurisdictions, 316 individuals travelling across 15 bioregions and six kingfish moving between Australia and NZ. Our findings provide important new insights into the structure and connectivity of the eastern Australia kingfish stock and suggest increased collaboration between state and international fisheries jurisdictions may support improved stock assessment and management.

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Drivers of population dynamics of at-risk populations change with pathogen arrival - Alexander T. Grimaudo; Joseph R. Hoyt; R. Andrew King; Rickard S. Toomey; Chris Simpson; Cory Holliday; Alexander Silvis; Rick T. Doyle; Joseph A. Kath; Mike P. Armstrong; Virgil Brack; Richard J. Reynolds; et al. (Biological Conservation, 2024)

Association of physical function with connectivity in the sensorimotor and dorsal attention networks: why examining specific components of physical function matters - Madeline C. Boyd; Jonathan H. Burdette; Michael E. Miller; Robert G. Lyday; Christina E. Hugenschmidt; W. Jack Rejeski; Sean L. Simpson; Laura D. Baker; Chal E. Tomlinson; Stephen B. Kritchevsky; Paul J. Laurienti (GeroScience, 2024)
Declining physical function with aging is associated with structural and functional brain network organization. Gaining a greater understanding of network associations may be useful for targeting interventions that are designed to slow or prevent such decline. Our previous work demonstrated that the Short Physical Performance Battery (eSPPB) score and body mass index (BMI) exhibited a statistical interaction in their associations with connectivity in the sensorimotor cortex (SMN) and the dorsal attention network (DAN). The current study examined if components of the eSPPB have unique associations with these brain networks. Functional magnetic resonance imaging was performed on 192 participants in the BNET study, a longitudinal and observational trial of community-dwelling adults aged 70 or older. Functional brain networks were generated for resting state and during a motor imagery task. Regression analyses were performed between eSPPB component scores (gait speed, complex gait speed, static balance, and lower extremity strength) and BMI with SMN and DAN connectivity. Gait speed, complex gait speed, and lower extremity strength significantly interacted with BMI in their association with SMN at rest. Gait speed and complex gait speed were interacted with BMI in the DAN at rest while complex gait speed, static balance, and lower extremity strength interacted with BMI in the DAN during motor imagery. Results demonstrate that different components of physical function, such as balance or gait speed and BMI, are associated with unique aspects of brain network organization. Gaining a greater mechanistic understanding of the associations between low physical function, body mass, and brain physiology may lead to the development of treatments that not only target specific physical function limitations but also specific brain networks.

Olfactory tract/bulb metal concentration in Manganese-exposed mineworkers - Luis F. Gonzalez-Cuyar; Gill Nelson; Susan Searles Nielsen; Wendy W. Dlamini; Amelia Keyser-Gibson; C. Dirk Keene; Michael Paulsen; Susan R. Criswell; Natalie Senini; Lianne Sheppard; Shar Samy; Christopher D. Simpson; et al. (NeuroToxicology, 2024)

Description and taxonomic assessment of fossil Cercopithecidae from the Pliocene Galili Formation (Ethiopia) - Hailay G. Reda; Stephen R. Frost; Evan A. Simons; Jay Quade; Scott W. Simpson (Journal of Human Evolution, 2024)

Bioprotective lactobacilli in Crescenza and Gouda cheese models to inhibit fungal spoilage - Zheng Zhao; David J. Simpson; Michael G. Gänzle (International Dairy Journal, 2024)

Analysis of natural organic matter chemistry in bentonite clay under compaction using different dry densities and duration - Meiling Man; Huan Tong; Nivetha Srikanthan; Muhammed O. Usman; Claire S. Tully; James J. Noël; Mehran Behazin; W. Jeffrey Binns; Peter G. Keech; Myrna J. Simpson (Applied Geochemistry, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Distinct dynamics of plant- and microbial-derived soil organic matter in relation to varying climate and soil properties in temperate agroecosystems - Meiling Man; Edward G. Gregorich; Michael H. Beare; Benjamin H. Ellert; Myrna J. Simpson (Geochimica et Cosmochimica Acta, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Deficiency of the mitochondrial ribosomal subunit, MRPL50, causes autosomal recessive syndromic premature ovarian insufficiency - Shabnam Bakhshalizadeh; Daniella H. Hock; Nicole A. Siddall; Brianna L. Kline; Rajini Sreenivasan; Katrina M. Bell; Franca Casagranda; Sadishkumar Kamalanathan; Jayaprakash Sahoo; Niya Narayanan; Dukhabandhu Naik; Varun Suryadevara; et al. (Human Genetics, 2023)
Premature ovarian insufficiency (POI) is a common cause of infertility in women, characterised by amenorrhea and elevated FSH under the age of 40 years. In some cases, POI is syndromic in association with other features such as sensorineural hearing loss in Perrault syndrome. POI is a heterogeneous disease with over 80 causative genes known so far; however, these explain only a minority of cases. Using whole-exome sequencing (WES), we identified a MRPL50 homozygous missense variant (c.335T > A; p.Val112Asp) shared by twin sisters presenting with POI, bilateral high-frequency sensorineural hearing loss, kidney and heart dysfunction. MRPL50 encodes a component of the large subunit of the mitochondrial ribosome. Using quantitative proteomics and western blot analysis on patient fibroblasts, we demonstrated a loss of MRPL50 protein and an associated destabilisation of the large subunit of the mitochondrial ribosome whilst the small subunit was preserved. The mitochondrial ribosome is responsible for the translation of subunits of the mitochondrial oxidative phosphorylation machinery, and we found patient fibroblasts have a mild but significant decrease in the abundance of mitochondrial complex I. These data support a biochemical phenotype associated with MRPL50 variants. We validated the association of MRPL50 with the clinical phenotype by knockdown/knockout of mRpL50 in Drosophila , which resulted abnormal ovarian development. In conclusion, we have shown that a MRPL50 missense variant destabilises the mitochondrial ribosome, leading to oxidative phosphorylation deficiency and syndromic POI, highlighting the importance of mitochondrial support in ovarian development and function.

Venom phenotype conservation suggests integrated specialization in a lizard-eating snake - Tucker C. Heptinstall; Jason L. Strickland; Ramses A. Rosales-Garcia; Rhett M. Rautsaw; Cassandra L. Simpson; Gunnar S. Nystrom; Schyler A. Ellsworth; Michael P. Hogan; Miguel Borja; Pollyanna Fernandes Campos; Felipe G. Grazziotin; Darin R. Rokyta; et al. (Toxicon, 2023)

Nitrogen Addition Increases Freeze Resistance in Black Mangrove (Avicennia germinans) Shrubs in a Temperate-Tropical Ecotone - Ilka C. Feller; Uta Berger; Samantha K. Chapman; Emily M. Dangremond; Nicole G. Dix; J. Adam Langley; Catherine E. Lovelock; Todd Z. Osborne; Audrey C. Shor; Loraé T. Simpson (Ecosystems, 2023)

Thermal Profiles: Novel phenotypic measurements of animal growth and metabolic efficiency - A.L. Schaefer; O. Iheshiulor; H. von Gaza; P. Charagu; G. Simpson; A. Huisman (Journal of Thermal Biology, 2023)

Generalized moisture diffusivity for food drying through multiscale modeling - Zachary G. Welsh; Matthew J. Simpson; Md Imran H. Khan; M.A. Karim (Journal of Food Engineering, 2023)

Optimization and Scale Up of Spray Dried CPZEN-45 Aerosol Powders for Inhaled Tuberculosis Treatment - Ian E. Stewart; Phillip G. Durham; Jacob M. Sittenauer; Aranza P. Barreda; Grayson W. Stowell; Carmella Moody; Jeffery B. Mecham; Catherine Simpson; Sharon Daily; Sara E. Maloney; Mark D. Williams; Diana Severynse-Stevens; et al. (Pharmaceutical Research, 2022)

Fire‐related threats and transformational change in Australian ecosystems - David A. Keith; Stuart P. Allen; Rachael V. Gallagher; Berin D. E. Mackenzie; Tony D. Auld; Sarah Barrett; Anne Buchan; Valerie English; Carl Gosper; Dave Kelly; Allen McIllwee; Rachel T. Melrose; et al. (Global Ecology and Biogeography, 2022)
Aim Megafire events generate immediate concern for wildlife and human well‐being, but their broader ecological impacts likely extend beyond individual species and single fire events. In the first mechanistic study of fire effects focussed on ecosystems, we aimed to assess the sensitivity and exposure of ecosystems to multiple fire‐related threats, placing impacts in the context of changing fire regimes and their interactions with other threats. Location Southern and eastern Australia. Time period 2019–2020. Major species studied Australian ecosystems. Methods We defined 15 fire‐related threats to ecosystems based on mechanisms associated with: (a) direct effects of fire regime components; (b) interactions between fire and physical environmental processes; (c) effects of fire on biological interactions; and (d) interactions between fire and human activity. We estimated the sensitivity and exposure of a sample of 92 ecosystem types to each threat type based on published relationships and spatial analysis of the 2019–2020 fires. Results Twenty‐nine ecosystem types assessed had more than half of their distribution exposed to one or more threat types, and only three of those were listed as nationally threatened. Three fire‐related threat types posed the most severe threats to large numbers of ecosystem types: high frequency fire; pre‐fire drought; and post‐fire invasive predator activity. The ecosystem types most affected ranged from rain forests to peatlands, and included some, such as sclerophyllous eucalypt forests and heathlands, that are traditionally regarded as fire‐prone and fire‐adapted. Main conclusions Most impacts of the 2019–2020 fires on ecosystems became apparent only when they were placed in the context of the whole fire regime and its interactions with other threatening processes, and were not direct consequences of the megafire event itself. Our mechanistic approach enables ecosystem‐specific management responses for the most threatened ecosystem types to be targeted at underlying causes of degradation and decline.

Extinction risk, reconstructed catches and management of chondrichthyan fishes in the Western Central Atlantic Ocean - Brendan S. Talwar; Brooke Anderson; Cristopher G. Avalos‐Castillo; María del Pilar Blanco‐Parra; Alejandra Briones; Diego Cardeñosa; John K. Carlson; Patricia Charvet; Charles F. Cotton; Zoe Crysler; Danielle H. Derrick; Michael R. Heithaus; et al. (Fish and Fisheries, 2022)
Chondrichthyan fishes are among the most threatened vertebrates on the planet because many species have slow life histories that are outpaced by intense fishing. The Western Central Atlantic Ocean, which includes the Greater Caribbean, is a hotspot of chondrichthyan biodiversity and abundance, but has been characterized by extensive shark and ray fisheries and a lack of sufficient data for effective management and conservation. To inform future research and management decisions, we analysed patterns in chondrichthyan extinction risk, reconstructed catches and management engagement in this region. We summarized the extinction risk of 180 sharks, rays and chimaeras, including 66 endemic and 14 near‐endemic species, using contemporary IUCN Red List assessments. Over one‐third (35.6%) were assessed as Vulnerable, Endangered or Critically Endangered, primarily due to overfishing. Reconstructed catches from 1950 to 2016 peaked in 1992, then declined by 40.2% thereafter. The United States, Venezuela and Mexico were responsible for most catches in the region and hosted the largest proportions of the regional distributions of threatened species, largely due to having extensive coastal habitats in their Exclusive Economic Zones. The quantity and taxonomic resolution of fisheries landings data were poor in much of the region, and national‐level regulations varied widely across jurisdictions. Deepwater fisheries represent an emerging threat, although many deepwater chondrichthyans currently have refuge beyond the depths of most fisheries. Regional collaboration as well as effective and enforceable management informed by more complete fisheries data, particularly from small‐scale fisheries, are required to protect and recover threatened species and ensure sustainable fisheries.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Aortic haemodynamics: the effects of habitual endurance exercise, age and muscle sympathetic vasomotor outflow in healthy men - Denis J. Wakeham; Tony G. Dawkins; Rachel N. Lord; Jack S. Talbot; Freya M. Lodge; Bryony A. Curry; Lydia L. Simpson; Christopher J. A. Pugh; Robert E. Shave; Jonathan P. Moore (European Journal of Applied Physiology, 2022)
Purpose We determined the effect of habitual endurance exercise and age on aortic pulse wave velocity (aPWV), augmentation pressure (AP) and systolic blood pressure (aSBP), with statistical adjustments of aPWV and AP for heart rate and aortic mean arterial pressure, when appropriate. Furthermore, we assessed whether muscle sympathetic nerve activity (MSNA) correlates with AP in young and middle-aged men. Methods Aortic PWV, AP, aortic blood pressure (applanation tonometry; SphygmoCor) and MSNA (peroneal microneurography) were recorded in 46 normotensive men who were either young or middle-aged and endurance-trained runners or recreationally active nonrunners (10 nonrunners and 13 runners within each age-group). Between-group differences and relationships between variables were assessed via ANOVA/ANCOVA and Pearson product-moment correlation coefficients, respectively. Results Adjusted aPWV and adjusted AP were similar between runners and nonrunners in both age groups (all, P > 0.05), but higher with age (all, P < 0.001), with a greater effect size for the age-related difference in AP in runners (Hedges’ g , 3.6 vs 2.6). aSBP was lower in young ( P = 0.009; g = 2.6), but not middle-aged ( P = 0.341; g = 1.1), runners compared to nonrunners. MSNA burst frequency did not correlate with AP in either age group (young: r = 0.00, P = 0.994; middle-aged: r = − 0.11, P = 0.604). Conclusion There is an age-dependent effect of habitual exercise on aortic haemodynamics, with lower aSBP in young runners compared to nonrunners only. Statistical adjustment of aPWV and AP markedly influenced the outcomes of this study, highlighting the importance of performing these analyses. Further, peripheral sympathetic vasomotor outflow and AP were not correlated in young or middle-aged normotensive men.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Determining tolerance levels for quality assurance of 3D printed bolus for modulated arc radiotherapy of the nose - T. Kairn; S. Talkhani; P. H. Charles; B. Chua; C. Y. Lin; A. G. Livingstone; S. K. Maxwell; T. Poroa; E. Simpson-Page; E. Spelleken; M. Vo; S. B. Crowe (Physical and Engineering Sciences in Medicine, 2021)

The Toxicology Investigators Consortium 2020 Annual Report - Meghan B. Spyres; Kim Aldy; Lynn A Farrugia; A. Min Kang; Jennifer S. Love; Sharan L. Campleman; Shao Li; Alexandra Amaducci; Evan Schwarz; Paul M. Wax; Jeffery Brent; J. Acciani; et al. (Journal of Medical Toxicology, 2021)

Mineralogical and Micro-structural Investigation into the Mechanical Behaviour of a Soft Calcareous Mudstone - D. Simpson; M. Rouainia; G. Elia (Rock Mechanics and Rock Engineering, 2021)
The construction industry in Abu Dhabi is thriving and its coastline has some of the most ambitious structures in the world. Whilst the subsurface evaporitic and calcareous soft rocks of this region are of great geological interest, they are relatively poorly understood from a geotechnical engineering perspective, forcing foundation designs to be overly conservative. Understanding the stiffness of the underlying geology at small strains is of great importance for the accurate estimation of ground movements around excavations and foundations, and yet routine post-SI laboratory testing programmes tend to focus on basic rock mechanics tests such as UCS tests. These procedures are generally unsuitable for use with calcareous rocks due to their friable and moisture sensitive nature, and rarely obtain parameters representative of actual in situ behaviour. The calcareous mudstone investigated in this paper has mechanical and structural characteristics falling between those of a soil and those typical of a rock and, as such, requires a geotechnical testing approach that combines methods from both soil and rock mechanics disciplines. The mineralogical, micro-structural and mechanical characteristics of this lithology have been examined via a suite of testing techniques, including XRPD, SEM, advanced triaxial with bender elements, along with industry standard procedures. Shearing, tensile and consolidation behaviours have been explored. Examination of the micro- and macro-scale features of this material shows it to be highly structured, with strength and stiffness being controlled by inter-granular bonding of Dolomite grains, as well as by mean effective stress state and rate of strain. The presence of fibrous Palygorskite acts to reduce the degree of bonding, causing specimens rich in this clay mineral to have a more ductile mechanical behaviour.

Development of Redwood Regeneration after Conifer Partial Harvest and Hardwood Management - John-Pascal Berrill; Lynn A Webb; Kristy L DeYoung; Christa M Dagley; Christopher G Bodle; Sean M Simpson (Forest Science, 2021)
Harvesting of commercial conifer species from conifer-hardwood mixtures can leave residual stands dominated by hardwoods. Removing unwanted hardwoods by cutting or herbicide makes growing space available to residual trees and regeneration and can restore conifer dominance. Forest managers of north coastal California need guidance on how such treatments affect subsequent growth of planted redwoods (Sequoia sempervirens [D. Don.] Endl.) or natural regeneration, as well as proliferation of undesirable species. Our observational study reconstructed growth of 108 regenerating redwoods in 26 treated stands. Residual stand density was the main driver of height and diameter growth in the new cohort of redwoods, irrespective of whether hardwoods were cut or received herbicide frill treatment (prevents resprouting). At lower residual stand densities, there were higher densities of natural regeneration (ingrowth) of conifers and hardwoods, which affected diameter at breast height (dbh) growth of regenerating redwoods. After heavier cutting of hardwoods, this ingrowth comprised a greater proportion of unwanted hardwood regeneration. Therefore, frill treatment is recommended when the objective of management is to reduce hardwood stocking and regeneration. Combining partial harvesting of conifers with cutting or frill treatment of hardwood is another option that reduces stand density to promote height and dbh growth of regenerating redwoods.

Zircon petrochronology in large igneous provinces reveals upper crustal contamination processes: new U–Pb ages, Hf and O isotopes, and trace elements from the Central Atlantic magmatic province (CAMP) - J. H. F. L. Davies; A. Marzoli; H. Bertrand; N. Youbi; M. Ernesto; N. D. Greber; M. Ackerson; G. Simpson; A.-S. Bouvier; L. Baumgartner; T. Pettke; F. Farina; et al. (Contributions to Mineralogy and Petrology, 2021)
Zircon occasionally crystallizes in evolved melt pockets in mafic large igneous province (LIP) magmas, and in these cases, it is used to provide high-precision age constraints on LIP events. The precision and accuracy of high-precision ages from LIPs are crucially important, because they may be implicated in mass extinctions. However, why zircon crystallizes in these magmas is not clearly understood, since their mafic compositions should limit zircon saturation. Here, we investigate the occurrence of zircon (and baddeleyite) in intrusive and extrusive mafic rocks from Central Atlantic Magmatic Province (CAMP) using petrography, trace-element analysis, Ti temperatures, Hf and oxygen isotopes, and high-precision U–Pb geochronology, along with petrological and thermal modeling. We provide new ages for CAMP sills that intruded into Paleozoic sediments in Brazil, indicating that the high and low Ti magmatism in this area occurred synchronously over 264 ± 57 ka. We show that upper crustal assimilation, especially of shales, during the emplacement of the CAMP likely led to zircon saturation. Assimilation of upper crustal sediments is also supported by high δ 18 O values and some rare negative εHf values in the zircon crystals. The only extrusive sample analyzed was the North Mountain basalt in Nova Scotia, Canada. This sample contains a large age variation in its zircon crystals (up to 4 Ma), and the older crystals have slightly more negative εHf values suggesting the presence of small (micron scale) xenocrystic cores associated with very late-stage sediment assimilation. However, the CAMP dataset as a whole suggests that the presence of xenocrystic cores is rare. Assuming no xenocrystic cores, and considering the zircon undersaturated nature of LIP mafic melts, the oldest zircon age clusters in a population should record the magma emplacement (or time when assimilation occurred), and the younger ages in a population are more likely to reflect Pb loss, especially given the high U concentrations of LIP zircon. Our identification of heterogeneous isotopic and elemental compositions in LIP zircon indicates that zircon in these magmas saturate in isolated minute melt pockets just before the system cools below its solidus.

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

The impact of acute and chronic exercise on Nrf2 expression in relation to markers of mitochondrial biogenesis in human skeletal muscle - Hashim Islam; Jacob T. Bonafiglia; Patrick C. Turnbull; Craig A. Simpson; Christopher G. R. Perry; Brendon J. Gurd (European Journal of Applied Physiology, 2020)

Molecular Diagnosis of Emmonsia-Like Fungi Occurring in Wild Animals - P. Danesi; C. Falcaro; K. Dukik; Y. Jiang; A. P. Rizzoli; R. Allavena; V. Simpson; S. Ravagnan; C. Zanardello; G. Capelli; G. S. de Hoog (Mycopathologia, 2019)

Comparison of metabolomic responses of earthworms to sub-lethal imidacloprid exposure in contact and soil tests - Vivek D. Dani; Brian P. Lankadurai; Edward G. Nagato; André J. Simpson; Myrna J. Simpson (Environmental Science and Pollution Research, 2019)

Parents’ views of genetic testing and treatment of familial hypercholesterolemia in children: a qualitative study - Karen Forrest Keenan; Robert M. Finnie; William G. Simpson; Lorna McKee; John Dean; Zosia Miedzybrodzka (Journal of Community Genetics, 2019)

Regional variability in the atmospheric nitrogen deposition signal and its transfer to the sediment record in Greenland lakes - N. J. Anderson; C. J. Curtis; E. J. Whiteford; V. J. Jones; S. McGowan; G. L. Simpson; J. Kaiser (Limnology and Oceanography, 2018)
Disruption of the nitrogen cycle is a major component of global environmental change. δ 15 N in lake sediments is increasingly used as a measure of reactive nitrogen input but problematically, the characteristic depleted δ 15 N signal is not recorded at all sites. We used a regionally replicated sampling strategy along a precipitation and N‐deposition gradient in SW Greenland to assess the factors determining the strength of δ 15 N signal in lake sediment cores. Analyses of snowpack N and δ 15 N‐NO 3 and water chemistry were coupled with bulk sediment δ 15 N. Study sites cover a gradient of snowpack δ 15 N (ice sheet: −6‰; coast 10‰), atmospheric N deposition (ice sheet margin: ∼ 0.2 kg ha −1 yr −1 ; coast: 0.4 kg ha −1 yr −1 ) and limnology. Three 210 Pb‐dated sediment cores from coastal lakes showed a decline in δ 15 N of ca. 1‰ from ∼ 1860, reflecting the strongly depleted δ 15 N of snowpack N, lower in‐lake total N (TN) concentration (∼ 300 μ g N L −1 ) and a higher TN‐load. Coastal lakes have 3.7–7.1× more snowpack input of nitrate than inland sites, while for total deposition the values are 1.7–3.6× greater for lake and whole catchment deposition. At inland sites and lakes close to the ice‐sheet margin, a lower atmospheric N deposition rate and larger in‐lake TN pool resulted in greater reliance on N‐fixation and recycling (mean sediment δ 15 N is 0.5–2.5‰ in most inland lakes; n = 6). The primary control of the transfer of the atmospheric δ 15 N deposition signal to lake sediments is the magnitude of external N inputs relative to the in‐lake N‐pool.

A cross correlation method for chemical profiles in minerals, with an application to zircons of the Kilgore Tuff (USA) - L. C. Probst; T. E. Sheldrake; M. J. Gander; G. Wallace; G. Simpson; L. Caricchi (Contributions to Mineralogy and Petrology, 2018)

Fishes in a changing world: learning from the past to promote sustainability of fish populations - T. A. C. Gordon; H. R. Harding; F. K. Clever; I. K. Davidson; W. Davison; D. W. Montgomery; R. C. Weatherhead; F. M. Windsor; J. D. Armstrong; A. Bardonnet; E. Bergman; J. R. Britton; et al. (Journal of Fish Biology, 2018)
Populations of fishes provide valuable services for billions of people, but face diverse and interacting threats that jeopardize their sustainability. Human population growth and intensifying resource use for food, water, energy and goods are compromising fish populations through a variety of mechanisms, including overfishing, habitat degradation and declines in water quality. The important challenges raised by these issues have been recognized and have led to considerable advances over past decades in managing and mitigating threats to fishes worldwide. In this review, we identify the major threats faced by fish populations alongside recent advances that are helping to address these issues. There are very significant efforts worldwide directed towards ensuring a sustainable future for the world's fishes and fisheries and those who rely on them. Although considerable challenges remain, by drawing attention to successful mitigation of threats to fish and fisheries we hope to provide the encouragement and direction that will allow these challenges to be overcome in the future.

Mapping and expression of genes associated with raspberry fruit ripening and softening - Craig G. Simpson; Danny W. Cullen; Christine A. Hackett; Kay Smith; Paul D. Hallett; Jim McNicol; Mary Woodhead; Julie Graham (Theoretical and Applied Genetics, 2017)

Using exposure windows to explore an elusive biomarker: blood manganese - Marissa G. Baker; Bert Stover; Christopher D. Simpson; Lianne Sheppard; Noah S. Seixas (International Archives of Occupational and Environmental Health, 2016)

Enigmatic spheres from the Upper Triassic Lockatong Formation, Newark Basin of eastern Pennsylvania: evidence for microbial activity in marginal-lacustrine strandline deposits - Edward L. Simpson; David L. Fillmore; Michael J. Szajna; Emily Bogner; Margariete G. Malenda; Kelsey M. Livingston; Brian Hartline (Palaeobiodiversity and Palaeoenvironments, 2015)

Prioritization of knowledge needs for sustainable aquaculture: a national and global perspective - Aisla C Jones; Angela Mead; Michel J Kaiser; Melanie C V Austen; Alex W Adrian; Neil A Auchterlonie; Kenneth D Black; Lucy R Blow; Charlotte Bury; Janet H Brown; Gavin M Burnell; Elaine Connolly; et al. (Fish and Fisheries, 2015)
Aquaculture is currently the fastest expanding global animal food production sector and is a key future contributor to food security. An increase in food security will be dependent upon the development and improvement of sustainable practices. A prioritization exercise was undertaken, focusing on the future knowledge needs to underpin UK sustainable aquaculture (both domestic and imported products) using a ‘task force’ group of 36 ‘practitioners’ and 12 ‘research scientists’ who have an active interest in sustainable aquaculture. A long list of 264 knowledge needs related to sustainable aquaculture was developed in conjunction with the task force. The long list was further refined through a three stage process of voting and scoring, including discussions of each knowledge need. The top 25 knowledge needs are presented, as scored separately by ‘practitioners’ or ‘research scientists’. There was similar agreement in priorities identified by these two groups. The priority knowledge needs will provide guidance to structure ongoing work to make science accessible to practitioners and help to prioritize future science policy needs and funding. The process of knowledge exchange, and the mechanisms by which this can be achieved, effectively emerged as the top priority for sustainable aquaculture. Viable alternatives to wild fish‐based aquaculture feeds, resource constraints that will potentially limit expansion of aquaculture, sustainable offshore aquaculture and the treatment of sea lice also emerged as strong priorities. Although the exercise was focused on UK needs for sustainable aquaculture, many of the emergent issues are considered to have global application.

Marine extinction risk shaped by trait–environment interactions over 500 million years - Emily A. Orzechowski; Rowan Lockwood; Jarrett E. K. Byrnes; Sean C. Anderson; Seth Finnegan; Zoe V. Finkel; Paul G. Harnik; David R. Lindberg; Lee Hsiang Liow; Heike K. Lotze; Craig R. McClain; Jenny L. McGuire; et al. (Global Change Biology, 2015)
Perhaps the most pressing issue in predicting biotic responses to present and future global change is understanding how environmental factors shape the relationship between ecological traits and extinction risk. The fossil record provides millions of years of insight into how extinction selectivity (i.e., differential extinction risk) is shaped by interactions between ecological traits and environmental conditions. Numerous paleontological studies have examined trait‐based extinction selectivity; however, the extent to which these patterns are shaped by environmental conditions is poorly understood due to a lack of quantitative synthesis across studies. We conducted a meta‐analysis of published studies on fossil marine bivalves and gastropods that span 458 million years to uncover how global environmental and geochemical changes covary with trait‐based extinction selectivity. We focused on geographic range size and life habit (i.e., infaunal vs. epifaunal), two of the most important and commonly examined predictors of extinction selectivity. We used geochemical proxies related to global climate, as well as indicators of ocean acidification, to infer average global environmental conditions. Life‐habit selectivity is weakly dependent on environmental conditions, with infaunal species relatively buffered from extinction during warmer climate states. In contrast, the odds of taxa with broad geographic ranges surviving an extinction (>2500 km for genera, >500 km for species) are on average three times greater than narrow‐ranging taxa (estimate of odds ratio: 2.8, 95% confidence interval = 2.3–3.5), regardless of the prevailing global environmental conditions. The environmental independence of geographic range size extinction selectivity emphasizes the critical role of geographic range size in setting conservation priorities.

Genome-wide association study for refractive astigmatism reveals genetic co-determination with spherical equivalent refractive error: the CREAM consortium - Qing Li; Robert Wojciechowski; Claire L. Simpson; Pirro G. Hysi; Virginie J. M. Verhoeven; Mohammad Kamran Ikram; René Höhn; Veronique Vitart; Alex W. Hewitt; Konrad Oexle; Kari-Matti Mäkelä; Stuart MacGregor; et al. (Human Genetics, 2015)

Parental occupational paint exposure and risk of childhood leukemia in the offspring: findings from the Childhood Leukemia International Consortium - Helen D. Bailey; Lin Fritschi; Catherine Metayer; Claire Infante-Rivard; Corrado Magnani; Eleni Petridou; Eve Roman; Logan G. Spector; Peter Kaatsch; Jacqueline Clavel; Elizabeth Milne; John D. Dockerty; et al. (Cancer Causes & Control, 2014)

Predicted responses of arctic and alpine ecosystems to altered seasonality under climate change - Jessica G Ernakovich; Kelly A. Hopping; Aaron B. Berdanier; Rodney T. Simpson; Emily J. Kachergis; Heidi Steltzer; Matthew D. Wallenstein (Global Change Biology, 2014)
Global climate change is already having significant impacts on arctic and alpine ecosystems, and ongoing increases in temperature and altered precipitation patterns will affect the strong seasonal patterns that characterize these temperature‐limited systems. The length of the potential growing season in these tundra environments is increasing due to warmer temperatures and earlier spring snow melt. Here, we compare current and projected climate and ecological data from 20 Northern Hemisphere sites to identify how seasonal changes in the physical environment due to climate change will alter the seasonality of arctic and alpine ecosystems. We find that although arctic and alpine ecosystems appear similar under historical climate conditions, climate change will lead to divergent responses, particularly in the spring and fall shoulder seasons. As seasonality changes in the Arctic, plants will advance the timing of spring phenological events, which could increase plant nutrient uptake, production, and ecosystem carbon (C) gain. In alpine regions, photoperiod will constrain spring plant phenology, limiting the extent to which the growing season can lengthen, especially if decreased water availability from earlier snow melt and warmer summer temperatures lead to earlier senescence. The result could be a shorter growing season with decreased production and increased nutrient loss. These contrasting alpine and arctic ecosystem responses will have cascading effects on ecosystems, affecting community structure, biotic interactions, and biogeochemistry.

Prevalence of polypharmacy in a Scottish primary care population - R. A. Payne; A. J. Avery; M. Duerden; C. L. Saunders; C. R. Simpson; G. A. Abel (European Journal of Clinical Pharmacology, 2014)

Next generation sequencing-based molecular diagnosis of retinitis pigmentosa: identification of a novel genotype-phenotype correlation and clinical refinements - Feng Wang; Hui Wang; Han-Fang Tuan; Duy H. Nguyen; Vincent Sun; Vafa Keser; Sara J. Bowne; Lori S. Sullivan; Hongrong Luo; Ling Zhao; Xia Wang; Jacques E. Zaneveld; et al. (Human Genetics, 2014)

Early response of the northeast subarctic Pacific plankton assemblage to volcanic ash fertilization - Josiane Mélançon; Maurice Levasseur; Martine Lizotte; Pierre Delmelle; Jay Cullen; Roberta C. Hamme; Angelica Peña; Kyle G. Simpson; Michael Scarratt; Jean-Éric Tremblay; Jie Zhou; Keith Johnson; et al. (Limnology and Oceanography, 2014)
Fe‐poor water collected at Sta. P20 in the Gulf of Alaska in June 2011 was enriched with different concentrations of volcanic ash (0.12, 1.2, and 10 mg L ‒1 ) from two subduction zone volcanoes, Kasatochi and Chaiten, and incubated onboard under in situ conditions for 6 d. The experimental setup also included a control (no addition) and a positive control (addition of 0.6 nmol L ‒1 FeSO 4 ). Following a 4 d lag period, there were increases in carbon fixation rates (up to a factor of 10) and chlorophyll a concentrations (up to a factor of 3) in the positive control and in the ash‐enriched (1.2 and 10 mg L ‒1 ) treatments. Diatoms dominated at the end of the incubations, but cyanobacteria, dinoflagellates, pelagophytes, and haptophytes were also stimulated by the presence of ash. Deposition of ∼ 1 mg ash L ‒1 , which is in the lower range of those estimated to have caused the August 2008 bloom following the eruption of the Kasatochi volcano in the Aleutian Islands, would suffice to trigger a bloom in the Gulf of Alaska.

The mammalian gene function resource: the international knockout mouse consortium - Allan Bradley; Konstantinos Anastassiadis; Abdelkader Ayadi; James F. Battey; Cindy Bell; Marie-Christine Birling; Joanna Bottomley; Steve D. Brown; Antje Bürger; Carol J. Bult; Wendy Bushell; Francis S. Collins; et al. (Mammalian Genome, 2012)

Large scale international replication and meta-analysis study confirms association of the 15q14 locus with myopia. The CREAM consortium - Virginie J. M. Verhoeven; Pirro G. Hysi; Seang-Mei Saw; Veronique Vitart; Alireza Mirshahi; Jeremy A. Guggenheim; Mary Frances Cotch; Kenji Yamashiro; Paul N. Baird; David A. Mackey; Robert Wojciechowski; M. Kamran Ikram; et al. (Human Genetics, 2012)

Transgenic Stra8-EYFP pigs: a model for developing male germ cell technologies - Jeffrey R. Sommer; Lauren R. Jackson; Sean G. Simpson; Edwin B. Collins; Jorge A. Piedrahita; Robert M. Petters (Transgenic Research, 2012)

Region‐wide changes in marine ecosystem dynamics: state‐space models to distinguish trends from step changes - Matthew Spencer; Nova Mieszkowska; Leonie A. Robinson; Stephen D. Simpson; Michael T. Burrows; Silvana N. R. Birchenough; Eva Capasso; Polly Cleall‐Harding; Julia Crummy; Callan Duck; Damien Eloire; Matthew Frost; et al. (Global Change Biology, 2012)
Regime shifts are sudden changes in ecosystem structure that can be detected across several ecosystem components. The concept that regime shifts are common in marine ecosystems has gained popularity in recent years. Many studies have searched for the step‐like changes in ecosystem state expected under a simple interpretation of this idea. However, other kinds of change, such as pervasive trends, have often been ignored. We assembled over 300 ecological time series from seven UK marine regions, covering two to three decades. We developed state‐space models for the first principal component of the time series in each region, a common measure of ecosystem state. Our models allowed both trends and step changes, possibly in combination. We found trends in three of seven regions and step changes in two of seven regions. Gradual and sudden changes are therefore important trajectories to consider in marine ecosystems.

Brain Iron Dysregulation and the Risk of Ageing White Matter Lesions - Ola H. Gebril; J. E. Simpson; Janine Kirby; Carol Brayne; Paul G. Ince (NeuroMolecular Medicine, 2011)

Juvenile coral reef fish use sound to locate habitats - C. A. Radford; J. A. Stanley; S. D. Simpson; A. G. Jeffs (Coral Reefs, 2011)

Occurrence and Concentration of Dissolved Silver in Rivers in England and Wales - A. Peters; P. Simpson; G. Merrington; K. Rothenbacher; L. Sturdy (Bulletin of Environmental Contamination and Toxicology, 2011)

Temporal change in UK marine communities: trends or regime shifts? - M. Spencer; S. N. R. Birchenough; N. Mieszkowska; L. A. Robinson; S. D. Simpson; M. T. Burrows; E. Capasso; P. Cleall‐Harding; J. Crummy; C. Duck; D. Eloire; M. Frost; et al. (Marine Ecology, 2011)
A regime shift is a large, sudden, and long‐lasting change in the dynamics of an ecosystem, affecting multiple trophic levels. There are a growing number of papers that report regime shifts in marine ecosystems. However, the evidence for regime shifts is equivocal, because the methods used to detect them are not yet well developed. We have collated over 300 biological time series from seven marine regions around the UK, covering the ecosystem from phytoplankton to marine mammals. Each time series consists of annual measures of abundance for a single group of organisms over several decades. We summarised the data for each region using the first principal component, weighting either each time series or each biological component ( e.g. plankton, fish, benthos) equally. We then searched for regime shifts using Rodionov’s regime shift detection (RSD) method, which found regime shifts in the first principal component for all seven marine regions. However, there are consistent temporal trends in the data for six of the seven regions. Such trends violate the assumptions of RSD. Thus, the regime shifts detected by RSD in six of the seven regions are likely to be artefacts caused by temporal trends. We are therefore developing more appropriate time series models for both single populations and whole communities that will explicitly model temporal trends and should increase our ability to detect true regime shift events.

A wide diversity of previously undetected free‐living relatives of diplomonads isolated from marine/saline habitats - Martin Kolisko; Jeffrey D. Silberman; Ivan Cepicka; Naoji Yubuki; Kiyotaka Takishita; Akinori Yabuki; Brian S. Leander; Isao Inouye; Yuji Inagaki; Andrew J. Roger; Alastair G. B. Simpson (Environmental Microbiology, 2010)
Summary Over the last 15 years classical culturing and environmental PCR techniques have revealed a modest number of genuinely new major lineages of protists; however, some new groups have greatly influenced our understanding of eukaryote evolution. We used culturing techniques to examine the diversity of free‐living protists that are relatives of diplomonads and retortamonads, a group of evolutionary and parasitological importance. Until recently, a single organism, Carpediemonas membranifera , was the only representative of this region of the tree. We report 18 new isolates of Carpediemonas ‐like organisms (CLOs) from anoxic marine sediments. Only one is a previously cultured species. Eleven isolates are conspecific and were classified within a new genus, Kipferlia n. gen. The remaining isolates include representatives of three other lineages that likely represent additional undescribed genera (at least). Small‐subunit ribosomal RNA gene phylogenies show that CLOs form a cloud of six major clades basal to the diplomonad‐retortamonad grouping (i.e. each of the six CLO clades is potentially as phylogenetically distinct as diplomonads and retortamonads). CLOs will be valuable for tracing the evolution of diplomonad cellular features, for example, their extremely reduced mitochondrial organelles. It is striking that the majority of CLO diversity was undetected by previous light microscopy surveys and environmental PCR studies, even though they inhabit a commonly sampled environment. There is no reason to assume this is a unique situation – it is likely that undersampling at the level of major lineages is still widespread for protists.

Comparison of reproductive development in triploid and diploid female rainbow trout Oncorhynchus mykiss - Y. Han; M. Liu; L. Lan Zhang; B. Simpson; G. Xue Zhang (Journal of Fish Biology, 2010)
The diploid rainbow trout Oncorhynchus mykiss reached sexual maturity 3 years after hatching and its oogenesis underwent four stages, which were oogonia, primary oocyte, secondary oocyte and egg. Reproductive development and hormone changes of 4 to 35 month‐old female O. mykiss were investigated using histological and radioimmunoassay methods in order to provide a theoretical and practical basis for the use of triploid female O. mykiss . The oogonium of the triploid female could develop into the oocytes of the prophase with abortion occurring later; the oogonium was surrounded by stroma cells to form the oogonium cluster and the gonads showed a virilescent tendency when the oogonium clusters were gradually replaced by spermatogenic‐like cytocysts. After 13 months, amounts of gonadotropic hormone (GtH‐I, GtH‐II) and oestradiol (17 β ‐E 2 ) in triploid females were lower than in diploid fish at corresponding time periods, but the amounts of testosterone (T) increased consistently after 21 months and were more than in diploid fish in the corresponding time periods ( P > 0·05). The infertility of triploid females resulted from meiosis failure, which caused developmental abortion of oocytes and oogonium formed cytocysts before the prophase oocytes. The cytocyst formation was due to the lack of the normal interaction of ovum and follicular cells, the development of follicular cells producing steroids were inhibited, the arylate path from T to 17 β ‐E 2 was interrupted, concentration of 17 β ‐E 2 decreased and concentration of T increased in the blood, the content of vitellogenin (Vg) decreased in the liver with a low 17 β ‐E 2 and high T caused to ovaries to show a tendency to be virilescent.

Characterization of halotolerant Bicosoecida and Placididea (Stramenopila) that are distinct from marine forms, and the phylogenetic pattern of salinity preference in heterotrophic stramenopiles - Jong Soo Park; Alastair G. B. Simpson (Environmental Microbiology, 2010)
Summary Recent culture‐based studies demonstrate the distinctiveness of the microbial eukaryote biota of very hypersaline environments. In contrast, microscopy‐based faunistic studies suggest that the biota of habitats of more moderate hypersalinity (60–150‰) overlaps substantially with that of marine environments, but this has barely been studied with modern techniques. To investigate the diversity and salinity tolerance range of these organisms, eight cultures of heterotrophic stramenopiles were established from (or from nearby) moderately hypersaline locations. These isolates represent five independent groups; Groups A, B and C are bicosoecids; Groups D and E belong to Placididea. One isolate (Group A) is a strain of the widespread marine species Cafeteria roenbergensis , and cannot grow above 100‰ salinity. The other isolates – Groups B–E – can all grow at 150–175‰ salinities and are probably moderate halophiles. Groups B–E all represent previously unsequenced species or even genera, although Group B is the sister group of the borderline extreme halophile Halocafeteria. The high level of novelty en countered suggests that moderately hypersaline environments may harbour a heterotrophic stramenopile biota distinct from that of marine environments. Interestingly, our new isolates are all most closely related to marine or halophilic forms, and our phylogenies show large clades defined by saline/non‐saline habitats within bicosoecids, placidomonads and related lineages. In particular, most freshwater/soil bicosoecids form one well‐supported clade. The sole major exception is Bicosoeca , which is intermixed with marine environmental sequences originally referred to as ‘MAST‐13’, which are from brackish water, not typical seawater. It seems that the freshwater/marine barrier has been crossed very few times in the evolutionary history of these heterotrophic stramenopile flagellates.

Seasonal foraging and piscivory by sympatric wild and hatchery-reared steelhead from an integrated hatchery program - William G. Simpson; Benjamen M. Kennedy; Kenneth G. Ostrand (Environmental Biology of Fishes, 2009)

Paleolimnological evidence of the effects on lakes of energy and mass transfer from climate and humans - Peter R. Leavitt; S. C. Fritz; N. J. Anderson; P. A. Baker; T. Blenckner; L. Bunting; J. Catalan; D. J. Conley; W. O. Hobbs; E. Jeppesen; A. Korhola; S. McGowan; et al. (Limnology and Oceanography, 2009)
The premise of this article is that climate effects on lakes can be quantified most effectively by the integration of process‐oriented limnological studies with paleolimnological research, particularly when both disciplines operate within a common conceptual framework. To this end, the energy (E)‐mass ( m ) flux framework (E m flux) is developed and applied to selected retrospective studies to demonstrate that climate variability regulates lake structure and function over diverse temporal and spatial scales through four main pathways: rapid direct transfer of E to the lake surface by irradiance, heat, and wind; slow indirect effects of E via changes in terrestrial development and subsequent m subsidies to lakes; direct influx of m as precipitation, particles, and solutes from the atmosphere; and indirect influx of water, suspended particles, and dissolved substances from the catchment. Sedimentary analyses are used to illustrate the unique effects of each pathway on lakes but suggest that interactions among mechanisms are complex and depend on the landscape position of lakes, catchment characteristics, the range of temporal variation of individual pathways, ontogenetic changes in lake basins, and the selective effects of humans on m transfers. In particular, preliminary synthesis suggests that m influx can overwhelm the direct effects of E transfer to lakes, especially when anthropogenic activities alter m subsidies from catchments.

Restoring depleted coral‐reef fish populations through recruitment enhancement: a proof of concept - A. Heenan; S. D. Simpson; M. G. Meekan; S. D. Healy; V. A. Braithwaite (Journal of Fish Biology, 2009)
To determine whether enhancing the survival of new recruits is a sensible target for the restorative management of depleted coral‐reef fish populations, settlement‐stage ambon damsel fish Pomacentrus amboinensis were captured, tagged and then either released immediately onto small artificial reefs or held in aquaria for 1 week prior to release. Holding conditions were varied to determine whether they affected survival of fish: half the fish were held in bare tanks (non‐enriched) and the other half in tanks containing coral and sand (enriched). Holding fish for this short period had a significantly positive effect on survivorship relative to the settlement‐stage treatment group that were released immediately. The enrichment of holding conditions made no appreciable difference on the survival of fish once released onto the reef. It did, however, have a positive effect on the survival of fish while in captivity, thus supporting the case for the provision of simple environmental enrichment in fish husbandry. Collecting and holding settlement‐stage fish for at least a week before release appear to increase the short‐term survival of released fish; whether it is an effective method for longer‐term enhancement of locally depleted coral‐reef fish populations will require further study.

Sequence stratigraphy of Jurassic strata in the lower Surat Basin succession, Queensland - K. L. Hoffmann; J. M. Totterdell; O. Dixon; G. A. Simpson; A. T. Brakel; A. T. Wells; J. L. Mckellar (Australian Journal of Earth Sciences, 2009)

In Silico Construction of a Protein Interaction Landscape for Nucleotide Excision Repair - Nancy Tran; Ping-Ping Qu; Dennis A. Simpson; Laura Lindsey-Boltz; Xiaojun Guan; Charles P. Schmitt; Joseph G. Ibrahim; William K. Kaufmann (Cell Biochemistry and Biophysics, 2009)

Phylogeny of Cyperaceae Based on DNA Sequence Data: Current Progress and Future Prospects - A. Muthama Muasya; David A. Simpson; G. Anthony Verboom; Paul Goetghebeur; Robert F. C. Naczi; Mark W. Chase; Erik Smets (The Botanical Review, 2009)

Alpha e-taxonomy: responses from the systematics community to the biodiversity crisis - S. J. Mayo; R. Allkin; W. Baker; V. Blagoderov; I. Brake; B. Clark; R. Govaerts; C. Godfray; A. Haigh; R. Hand; K. Harman; M. Jackson; et al. (Kew Bulletin, 2008)

Nocturnal relocation of adult and juvenile coral reef fishes in response to reef noise - S. D. Simpson; A. Jeffs; J. C. Montgomery; R. D. McCauley; M. G. Meekan (Coral Reefs, 2008)

Within-field variability of Fusarium head blight pathogens and their associated mycotoxins - X.-M. Xu; D. W. Parry; P. Nicholson; M. A. Thomsett; D. Simpson; S. G. Edwards; B. M. Cooke; F. M. Doohan; S. Monaghan; A. Moretti; G. Tocco; G. Mule; et al. (European Journal of Plant Pathology, 2007)

Effects of Light on Microalgae Concentrations and Selenium Uptake in Bivalves Exposed to Selenium-Amended Sediments - D. Schlenk; G. Batley; C. King; J. Stauber; M. Adams; S. Simpson; W. Maher; J. T. Oris (Archives of Environmental Contamination and Toxicology, 2007)

Chlorophyll fluorescence, root growth potential, and stomatal conductance as estimates of field performance potential in conifer seedlings - Sylvia J. L’Hirondelle; David G. Simpson; Wolfgang D. Binder (New Forests, 2007)

The effects of AZD3582 [4-(nitroxy)butyl-(2S)-2-(6-methoxy-2-naphthyl) propanoate], and naproxen on key pathogenic steps in NSAID-enteropathy in the rat - M. Walley; G. Sigthorsson; C. Hotz-Behofsits; R. Simpson; I. Bjarnason (Inflammopharmacology, 2007)

Halocafeteria seosinensis gen. et sp. nov. (Bicosoecida), a halophilic bacterivorous nanoflagellate isolated from a solar saltern - Jong S. Park; Byung C. Cho; Alastair G. B. Simpson (Extremophiles, 2006)

Overwinter Storability of Conifer Planting Stock: Operational Testing of Fall Frost Hardiness - Sylvia J. L’Hirondelle; David G. Simpson; Wolfgang D. Binder (New Forests, 2006)

Transplant tolerance: models, concepts and facts - Nicola J. Monk; Roseanna E. G. Hargreaves; Elizabeth Simpson; Julian P. Dyson; Stipo Jurcevic (Journal of Molecular Medicine, 2006)

Predominance and association of pathogenic fungi causing Fusarium ear blightin wheat in four European countries - X. -M. Xu; D. W. Parry; P. Nicholson; M. A. Thomsett; D. Simpson; S. G. Edwards; B. M. Cooke; F. M. Doohan; J. M. Brennan; A. Moretti; G. Tocco; G. Mule; et al. (European Journal of Plant Pathology, 2005)

Does behaviour explain the larval dispersal of coral reef fishes better than oceanography?– An individual based model simulation approach - S. D. Simpson; C. Dytham; M. G. Meekan (Journal of Fish Biology, 2003)
Until recently, oceanographic models have been used, with limited success, to predict the larval dispersal of coral reef fishes. Settlement‐stage larvae have been shown to be capable swimmers and have highly developed sensory organs. We built two simulation individual based models (IBMs) of larval dispersal in the Dampier Archipelago, Western Australia. One followed an oceanographic model, while the other was driven by behavioural constraints. We compare predictions of these models with an extensive dataset from a light‐trapping programme in an attempt to elucidate the overriding mechanism of larval coral reef fish dispersal.

Effects of administration of somatostatin‐14 and immunoneutralization of somatostatin on endocrine and growth responses in rainbow trout - B. C. Peterson; P. R. Simpson; K. D. Cain; R. H. Hardy; G. T. Schelling; T. L. Ott (Journal of Fish Biology, 2003)
Injection of somatostatin‐14 (SS‐14) at 5 ng g −1 body mass (BM) into rainbow trout Oncorhynchus mykiss decreased ( P r 2 = 0·54) levels of growth hormone (GH) (1·5 ± 0·9 ng ml −1 v. 6·6 ± 0·6 ng ml −1 ) over time when compared to controls. Somatostatin‐14 at 50 ng g −1 BM also decreased ( P = 0·064, q uadratic; r 2 = 0·30) levels of GH (3·6 ± 2·1 ng ml −1 v. 6·6 ± 0·6 ng ml −1 ) over time compared to controls. In a second study, passive immunization against SS‐14 (1 : 25 dose) increased ( P = 0·10, cubic, r 2 = 0·12) levels of GH (11·0 ± 4·8 ng ml −1 v. 5·2 ± 1·4 ng ml −1 ) over time. Passively immunizing against SS‐14 (1 : 50 dose) increased ( P r 2 = 0·10) levels of GH (8·2 ± 2·3 ng ml −1 v. 5·2 ± 1·4 ng ml −1 ) over time compared to controls. Overall, in the active immunization study there was no difference ( P > 0·10) in specific growth rate ( G ) or feed conversion ratio ( FCR ) between the three treatment groups during the 9 weeks of the study. Only four of the fish immunized against SS‐14, however, developed antibody titres against SS. Compared to controls, these fish exhibited a G of 0·89 ± 0·09 v. 0·56 ± 0·09% per 3 weeks and FCR of 0·80 ± 0·04 v. 1·20 ± 0·05 g g −1 . In SS‐14 immunized fish, levels of GH decreased ( P P G and FCR is dependent upon generation of antibody titres.

Analytical Model for Permeability Evolution in Microcracking Rock - G. D. H. Simpson; Y. Guéguen; F. Schneider (Pure and Applied Geophysics, 2003)

The Importance of Nitrogen Oxides for the Exceedance of Critical Thresholds in the Nordic Countries - M. Johansson; R. Suutari; J. Bak; G. Lövblad; M. Posch; D. Simpson; J.-P. Tuovinen; K. Tørseth (Water, Air, & Soil Pollution, 2001)

Poster Session - J. van S. Graver; H. J. Banks; A. K. Sharp; A. Contessi; N. Baldassari; M. Maggioli; Sabine Prozell; Ch. Reichmuth; Maria Otília Carvalho; Ana Paula Pereira; A. Mexia; Sylvia Allen; et al. (Phytoparasitica, 2001)

Phase relations, singularities and thermobarometry of metamorphic assemblages containing phengite, chlorite, biotite, K-feldspar, quartz and H2O - G. D. H. Simpson; A. B. Thompson; J. A. D. Connolly (Contributions to Mineralogy and Petrology, 2000)

Centrin in the groove: immunolocalisation of centrin and microtubules in the putatively primitive protistChilomastix cuspidata (Retortamonadida) - N. D. Weerakoon; J. D. I. Harper; A. G. B. Simpson; D. J. Patterson (Protoplasma, 1999)

Geochemistry of an arsenic anomaly in St. Elizabeth, Jamaica - G. Lalor; R. Rattray; P. Simpson; M.K. Vutchkov (Environmental Geochemistry and Health, 1999)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

The Validity of Similarity Theory in the Roughness Sublayer Above Forests - I. J. Simpson; G. W. Thurtell; H. H. Neumann; G. Den Hartog; G. C. Edwards (Boundary-Layer Meteorology, 1998)

Polarity of mutations in tumor-associated microsatellite instability - Rosane Sturzeneker; Luciana A. Haddad; Roberta A. U. Bevilacqua; Andrew J. G. Simpson; Sérgio D. J. Pena (Human Genetics, 1998)

Detection and Quantification of Individual Fungal Species in Fusarium Disease Complexes of Cereals by Polymerase Chain Reaction (PCR) - P. Nicholson; F. Doohan; H. N. Rezanoor; D. Simpson; P. H. Smith; A. Turner; G. Weston (Cereal Research Communications, 1997)

Does RGP predict field performance? A debate - David G. Simpson; Gary A. Ritchie (New Forests, 1997)

The role of glutathione in L -2-chloropropionic acid induced cerebellar granule cell necrosis in the rat - I. Wyatt; Andrew Gyte; Michael G. Simpson; Peter S. Widdowson; Edward A. Lock (Archives of Toxicology, 1996)

Book review: Potato diseases - F. E. Manzer; G. W. Simpson (American Journal of Potato Research, 1984)

Effect of time of inoculation with potato leafroll virus on development of net necrosis and stem-end browning in potato tubers - F. E. Manzer; D. C. Merriam; R. H. Storch; G. W. Simpson (American Journal of Potato Research, 1982)

Congo/Crimean Haemorrhagic Fever virus from Iraq 1979: I. Morphology in BHK21 cells - D. S. Ellis; T. Southee; G. Lloyd; G. S. Platt; Nicola Jones; Susan Stamford; E. T. W. Bowen; D. I. H. Simpson (Archives of Virology, 1981)

Growth characteristics of potato plants useful in studies of population dynamics and biological control of aphids - W. A. Shands; G. W. Simpson; Corinne C. Gordon (American Journal of Potato Research, 1971)

Penobscot: A new variety of potato with leafroll resistance and high solids - G. W. Simpson; R. V. Akeley (American Journal of Potato Research, 1964)

Exploratory tests to prevent leaf roll infection transmitted by aphids - W. A. Shands; G. W. Simpson (American Journal of Potato Research, 1964)

The relationship of aphid abundance on potato plants to the specific gravity of the tubers - W. A. Shands; G. W. Simpson (American Journal of Potato Research, 1962)

Report of editorial committee - Arthur Hawkins; Ora Smith; A. Frank Ross; R. E. Webb; G. W. Simpson; J. C. Campbell (American Journal of Potato Research, 1959)

The use of ethylene chlorohydrin for breaking the rest period of large quantities of potatoes - W. F. Porter; G. W. Simpson (American Journal of Potato Research, 1947)